A study of the impact of statins, ACE inhibitors and gastric acid suppressants on pneumonia risk and mortality using the Health Improvement Network Database - Myles, Puja Runa (2009)
Pneumonia is a common diagnosis in general practice and is associated with significant morbidity and mortality. Current estimates of pneumonia incidence in the UK are based on studies more than a decade ago and little is known about longer term outcomes in pneumonia patients. Though much is known about the aetiology of pneumonia and predictors of mortality, an emerging area for research is the relationship between commonly prescribed drugs in general practice and pneumonia.